Margot Fonteyn Book review - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Margot Fonteyn. The most difficult problem facing anyone writing about Fonteyn's life must be how to make sense of her marriage to Roberto Arias. PALABRAS CLAVE: Margot Fonteyn, life and career.
Dentro del apartado " Shelf Content".
Margot Fonteyn. Meredith Daneman, Viking, 2004.